(untitled) (Journal of Industrial and Mechanical Engineering, 2020)
The work presented below aims to advance on opportunities for the development of Innovation Driven Enterprises (IDE), or technology startups in Argentina to enrich the offer of products and services oriented to the Industry 4.0 or Smart Manufacturing paradigm as applicable in Europe or the United States. In this sense, according to the “Report on Systematic Conditions for Entrepreneurship in Latin America: Entrepreneurship and Digitization: A Common Possibility Agenda”, an opportunity appears to develop and strengthen the fabric of local technology-based companies taking into account the progress of the digitization in the industry, the drastic reduction in the costs of innovating and the ease of adoption of new technologies by users. On the other hand, it is of interest to inquire as to whether the local capacities for the development of technological systems demanded by the new model, and also whether the level of complexity and integration within each system can be achieved at the local or regional level. A reference of great interest for this work is that of Germany and the ecosystem around the Industry 4.0 paradigm. In particular, it becomes relevant from the development of the so-called Dual Strategy aimed at leadership in the industrial market and the offer of technology for the Industry 4.0 model, which is carried out by the publication of the Group of Communication Promoters of the German Industry-Science research alliance, recommendations for implementing the strategic initiative Industrie 4.0. Another interesting case is what happens in the United States and the technology startups that nurture the Smart Manufacturing model. In both cases, a concept that underlies the paradigm of Industry 4.0 and technology startups is that of the Innovation Ecosystem. After developing the concepts of Innovation ecosystem and the creation of technology-based companies, and innovation ecosystems in the world, this article will analyse innovation ecosystems in Argentina and analyse the situation against the hypotheses put forward by various authors and that are mentioned in the first paragraph.